2015
DOI: 10.1097/prs.0000000000001718
|View full text |Cite
|
Sign up to set email alerts
|

Financial Conflicts of Interest

Abstract: Investigators with a financial conflict of interest are significantly more likely to publish plastic surgery studies with a positive conclusion compared with investigators with no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Conversely, chairs and chiefs had the lowest engagement among leadership holders. This may be due to limited time, competing interests, and the concern of the perception of bias that occurs when physicians accept industry contributions [3,31,32]. Our findings also suggest that women receive significantly smaller total sums for speaker sponsorship than their male peers.…”
Section: Plos Onementioning
confidence: 65%
See 1 more Smart Citation
“…Conversely, chairs and chiefs had the lowest engagement among leadership holders. This may be due to limited time, competing interests, and the concern of the perception of bias that occurs when physicians accept industry contributions [3,31,32]. Our findings also suggest that women receive significantly smaller total sums for speaker sponsorship than their male peers.…”
Section: Plos Onementioning
confidence: 65%
“…The current climate of government austerity and reduced institutional funding [1] has augmented reliance on industry sponsorship as a means for research and innovation. Industrysurgeon collaborations can create opportunities that encourage scholarly impact, recognition, and invited speaker engagements [2][3][4]. For example, research funding has been shown to positively impact scholarly productivity [5][6][7], whereas sponsored speakerships reflect a surgeon's expertise and status as a key opinion leader [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some published reports have demonstrated that studies with COI as compared to studies with no COI are more likely to report favorable outcomes. Researchers with conflicts were more likely to selectively choose parameters that produce better results and to report larger magnitudes of differences versus researchers with no COI 5,17,18 . However, the effects of unreported COI on study results are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Self-disclosed conflicts-of-interest (COI) have been associated with the publication of favorable articles, defined as articles conveying a positive impression of a product produced by a company having an affiliation with at least 1 author. This bias influences the opinions and decisions of healthcare providers and patients 1,2,3,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The “funding effect” has been reported across a number of fields, including pharmaceuticals [ 8 ], chemical toxicology [ 9 ], tobacco [ 10 ], surgery [ 11 ], mobile phones [ 12 ], nutrition [ 13 ], and biotechnology. Diels et al (2011) examined research on genetically modified crops and found that “COIs through professional affiliations or direct research funding are likely to influence the final outcome of such studies in the commercial interest of the involved industry [ 14 ].…”
Section: Introductionmentioning
confidence: 99%